(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This article provides a comprehensive analysis of the legal framework governing intellectual property rights in Uzbekistan. It examines both domestic legislation and international treaties, with particular attention to the principles of enhanced intellectual property protection enshrined in the Constitution of New Uzbekistan and related legal acts.